Reducing water footprint of building sector: concrete with seawater and marine aggregates. (August 2019) - Arosio, V; Arrigoni, A; Dotelli, G
Abstract: Freshwater resources are currently under great pressure all over the world due to many factors, such as climate change and growing urbanization. Industrial products like concrete pauperize a significant share of available freshwater during their life cycle. Therefore, cutting down the amount of freshwater consumed by these products might be a solution to reduce the stress in regions affected by water scarcity. In this study, the potential freshwater savings linked to the adoption of innovative concrete mixtures were investigated via the Life Cycle Assessment (LCA) method. In particular, the use of marine aggregates instead of land-based ones and seawater rather than freshwater in the mixing process of concrete were examined. To improve the validity of the analysis, the applicability to the Italian context using geo-referenced data for the distance to the coastline and the availability of freshwater was explored. Results confirmed the positive effect that the use of seawater and marine aggregates might have in reducing the water footprint of the Italian construction sector, leaving freshwater available for human consumption. Mixing concrete with seawater would lead to a reduction of its water footprint up to 12%. Moreover, if land-won aggregates were replaced with marine ones, an 84% reduction of the water footprint could be achieved. In both cases, possible burden shifting (e.g. increase of greenhouse gases emissions) should be investigated.